Comparative Evaluation of Microleakage Between Nano-Ionomer, Giomer and Resin Modified Glass Ionomer Cement in Class V Cavities- CLSM Study - Bollu, Indira Priyadarshini (J Clin Diagn Res, 2016)
INTRODUCTION: Marginal integrity of adhesive restorative materials provides better sealing ability for enamel and dentin and plays an important role in success of restoration in Class V cavities. Restorative material with good marginal adaptation improves the longevity of restorations. AIM: Aim of this study was to evaluate microleakage in Class V cavities which were restored with Resin Modified Glass Ionomer Cement (RMGIC), Giomer and Nano-Ionomer. MATERIALS AND METHODS: This in-vitro study was performed on 60 human maxillary and mandibular premolars which were extracted for orthodontic reasons. A standard wedge shaped defect was prepared on the buccal surfaces of teeth with the gingival margin placed near Cemento Enamel Junction (CEJ). Teeth were divided into three groups of 20 each and restored with RMGIC, Giomer and Nano-Ionomer and were subjected to thermocycling. Teeth were then immersed in 0.5% Rhodamine B dye for 48 hours. They were sectioned longitudinally from the middle of cavity into mesial and distal parts. The sections were observed under Confocal Laser Scanning Microscope (CLSM) to evaluate microleakage. Depth of dye penetration was measured in millimeters. STATISTICAL ANALYSIS: The data was analysed using the Kruskal Wallis test. Pair wise comparison was done with Mann Whitney U Test. A p-value<0.05 is taken as statistically significant. RESULTS: Nano-Ionomer showed less microleakage which was statistically significant when compared to Giomer (p=0.0050). Statistically no significant difference was found between Nano Ionomer and RMGIC (p=0.3550). There was statistically significant difference between RMGIC and Giomer (p=0.0450). CONCLUSION: Nano-Ionomer and RMGIC showed significantly less leakage and better adaptation than Giomer and there was no statistically significant difference between Nano-Ionomer and RMGIC.